2013
DOI: 10.1002/dvdy.24032
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchanger 1 (NHE1) function is necessary for maintaining mammary tissue architecture

Abstract: Background: The mammary gland is an ideal model to study the link between form and function in normal tissue. Perhaps as interesting as the cues necessary to generate this structure are the signals required to maintain its branched architecture over the lifetime of the organism, since likely these pathways are de-regulated in malignancies. Previously, we have shown that the Na 1 /H 1 exchanger 1 (NHE1), a critical regulator of intracellular pH, was necessary for mammary branching morphogenesis. Here we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…So far, it is not known whether the process of decoupling itself is also regulated by an altered pH homoeostasis, induced, for example, by the BRAF V600E ‐mediated stimulation of NHE1 . Studies made with organoid cultures of mammary glands, however, revealed that the expression of E‐cadherin is downregulated by NHE1 inhibition …”
Section: Changes In Cell‐cell Communication Facilitate Tumour Progresmentioning
confidence: 99%
“…So far, it is not known whether the process of decoupling itself is also regulated by an altered pH homoeostasis, induced, for example, by the BRAF V600E ‐mediated stimulation of NHE1 . Studies made with organoid cultures of mammary glands, however, revealed that the expression of E‐cadherin is downregulated by NHE1 inhibition …”
Section: Changes In Cell‐cell Communication Facilitate Tumour Progresmentioning
confidence: 99%
“…The growth factor‐induced intracellular alkalization was blocked by the NHE1 specific inhibitor, MIA, and disrupted the mammary branching morphogenesis. In this model, treatment with MIA caused the whole primary mammary tissue acidification (Jenkins, Debnath, Varriano, Gundry, & Fata, 2014; Jenkins et al, 2012). Moreover, activation of NHE1 increased the pH i on the side of lamellipodia more than on the other side, and this gradient collapsed upon the inhibition of NHE1 (Denker & Barber, 2002).…”
Section: Discussionmentioning
confidence: 96%